Mixed states for mixing neutrinos - Cozzella, Gabriel [UNESP]; Giunti, Carlo (Amer Physical Soc, 2018)
Here we discuss the description of flavor neutrinos produced or detected in processes which involve more than one neutrino. We show that in these cases flavor neutrinos cannot be separately described by pure states, but require a density matrix description. We consider explicitly the examples of nu(e) and (nu) over bar (mu) production in mu(+) decay and nu(mu) detection through scattering on electrons. We show that the density matrix which describes a flavor neutrino can be approximated with a density matrix of a pure state only when the differences of the neutrino masses are neglected in the interaction process. In this approximation, the pure states are the standard flavor states and one recovers the standard expression for the neutrino oscillation probability. We discuss also the effects of mixing of the three standard light neutrinos with heavy neutrinos which can be either decoupled because their masses are much larger than the maximum neutrino energy in the neutrino production process or because they are produced and detected incoherently. Finally, we discuss the more complicated case of neutrino-electron elastic scattering, in which the initial and final neutrinos do not have determined flavors, but there is a flavor dependence due to the different contributions of charged-current and neutral-current interactions.